Association of C-reactive protein and D- dimer in patients with covid 19 (Journal of Pharmaceutical Negative Results, 2022)
Coronaviruses are enveloped non-segmented positive sense RNA viruses belonging to the coronaviridae family and order Nidovirales and broadly distributed in humans and other mammals. The out break of Corona virus disease (COVID-19) has affected more than 174,5 millions people in most countries this number reported by WHO till 12 June 2021 at 7:19 a.m. with mortality rate of 4.02% and has become a major global health concern. This study includes ( 124 ) COVID-19 patients , 40 females and 84 males, their ages range from 25 - 65 years old . Thirty-two apparently healthy individual were taken as a control group.As for measuring the concentration of C-reactive protein, the study showed that there was a high increase of C-reactive protein in patients with secondary and concomitant infection with the Corona virus, compared with the control group, and statistical analysis proved the existence of high significant differences and at the level of probability p ( 0.001 ).D-dimer is the principal breakdown fragment of fibrin and is used as a biomarker of fibrin formation and degradation, the study have shown that Ddimer is a valuable marker of activation of coagulation and fibrinolysis. There is increasing evidence that SARS- CoV-2 induces, a cytokine storm that triggers the coagulation cascade, causing thrombotic complications especialy in sever cases . This is clinically relevant as the activation of the coagulation cascade is a common feature of disseminated intravascular coagulation (DIC) and adverse clinical outcomes in COVID-19 patients and appears to be more frequent than what observed in patients suffering from severe forms of SARS- CoV in 2003.